The geological framework and depositional environments of the coal-bearing Karoo strata in the Central Kalahari Karoo Basin, Botswana - Segwabe, Tebogo (Rhodes University, Faculty of Science, Department of Geology, 2009)
The investigation of the geological history (i.e., stratigraphy and sedimentology) and the dynamics of coal depositional environments, in particular, the forces responsible for changes in the accommodation space (e.g., subsidence vs. sedimentation rates) in the Permian coal-bearing Karoo strata in the Central Kalahari Karoo Basin (Botswana) revealed new details about the depositional processes and environments. Detailed review of the temporal and spatial stratigraphic variation of the coal-bearing Ecca Group successions via the analysis of facies changes based on core descriptions, gamma logs, field observations and palaeo-current measurements, lead to the identification of two main informal stratigraphic units, namely the Basal and Upper Units. The Basal Unit is characterised by an upward-coarsening succession, and it is interpreted as a product of a progradational deltaic setting (i.e., regressive deltaic cycle). This is followed by five sequences of fining-upward successions of sandstones and siltstones in the Upper Unit, interpreted as deposits of distributary channels (the basal arenaceous member) capped by finer argillaceous sequences of the deltaic floodplains (the upper coal-bearing member). The Upper Unit thus is interpreted as a delta plain facies association which was formed during transgressive phases when conditions for coal-quality peat accumulation (e.g., high water table) were present and the available accommodation space was partly controlled by tectonic uplift (repeated?) at basin margins. Limited palaeo-current analysis indicates deposition by channels flowing from the east, south-east and north-east. The lack of good quality exposures hampers the reconstruction of the plan form of the channel patterns. However, the little available evidence indicates a high-energy fluvio-deltaic system with irregular discharge and a high proportion of bedload sediments. Coal-seam thickness in the upper coal-bearing member reflect the complex control of the geological processes associated with and following peat formation, such as differential compaction of the underlying lithology, and the erosive or protective nature of the immediately overlying lithology.
Keywords: Coal -- Geology -- Botswana; Sedimentation and deposition -- Botswana